Anther Culture Responses and Regeneration Efficiency in Five Indigenous Rice Genotypes of Bangladesh (Plant Tissue Culture and Biotechnology, 2026)
Anther culture is an efficient and reliable approach for the rapid production of doubled haploids (DHs) in rice and other cereal crops, enabling complete homozygous plants and accelerating genetic improvement. This study evaluated the androgenic responses of nineteen indigenous rice (Oryza sativa L.) genotypes from Bangladesh aiming to optimize the induction of embryoids, plant regeneration, and rooting efficiency. Among these materials Desi Lomba Atob, Chinigura, Krisnokoli, Buchi, and Surma exhibited positive callus responses. The highest number of embryoids (30.46 ± 0.75%) was achieved on N6 medium supplemented with 2.0 mg/l 2,4-D and 0.5 mg/l Kn, while the greatest shoot regeneration (20.80 ± 1.28%) was obtained in Krisnokoli on MS medium containing 2.0 mg/l BAP and 0.5 mg/l NAA. Krisnokoli also yielded the highest frequency of green plant regeneration, whereas Surma exhibited 100% albinism. Rooting was successfully induced on half-strength MS medium supplemented with 0.5 mg/l IBA, resulting in improved rooting efficiency. These findings highlight the strong genotypic influences on androgenic efficiency and emphasize the importance of hormonal optimization for DHs production. The optimized protocol and the superior response of Krisnokoli provide a valuable foundation for the conservation and genetic improvement of indigenous rice genotypes in Bangladesh through anther culture.Plant Tissue Cult. & Biotech. 36(1): 177-188, 2026 (June)